(untitled) (Journal of Health Sciences, 2023)
Introduction: Basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) are the most common skin malignancies in the heterogeneous group of non-melanoma skin cancer (NMSC). Due to increasing incidence these tumours remain significant health problem worldwide. Methods: We conducted retrospective analysis to evaluate the incidence of primary BCCs and SCCs in our institution from 2003 to 2022, and to correlate it with available clinical data. Results: We noticed that the incidence of NMSC increased between 2018 and 2022 (p<0.01). Among 1570 patients diagnosed with NMSC, BCC represented 77.9% of cases. BCC was constantly more common type of NMSC with statistically significant difference in the period from 2003-2005 and in the period from 2017- 2022 (p<0.01). Nodular subtype of the BCC was the most common, affecting primarily face. Superficial BCC occurred most commonly on trunk (p<0.01), affecting younger patients than the other histological subtypes (mean age 61.29±13.47 years (p<0.01). High-risk BCCs in men were more common on face and scalp (p<0.05). BCCs were predominantly smaller tumours (<2 cm) in contrast to SCCs with highest incidence in pT2-pT4 group (p<0.01). SCC patients were older (mean age 72.89±9.7) than BCC patients (mean age 65.15±12.80) (p<0.01). Conclusion: In order to improve prevention strategies and prevent further increase in incidence, there is need to develop current and exact registries of these malignancies, especially separately BCC and SCC.